BIOTIN DEFICIENCY IN TURKEY POULTS - ΔΕΣΠΟΤΟΠΟΥΛΟΣ Α.; ΔΕΜΕΡΤΖΗΣ Π.; ΜΑΓΚΟΥΤΑΣ Π. (Journal of the Hellenic Veterinary Medical Society, 1974)
An outbreak of leg weakness in turkey poults of the Larissa district (Central Greece) is described. Turkey poults at the age of on3 week were affected, the symptoms being more severe in male than in female. Chemical analysis of the used food disclosed low biotin content. Biotin addition to the food or drinking water prevented further cases. Tne increased needs for biotin in new breeds of turkeys are discussed under the light of recent knowledge on the subject.